Integrating Pancasila Values to Promote Anti-Corruption Ethics in Public Governance - Ramadhani, Shara Annisa; Mardatillah, Dwi; Oktavia, Dinah Suci; Putri, Alvina Aprilia (Jurnal Edukasi Terkini, 2026)
Purpose -This study aims to analyze how the implementation of Pancasila values shapes anti-corruption character within the government sector. It seeks to understand the extent to which these foundational national values guide ethical conduct, strengthen integrity, and foster accountability among civil servants, as well as to identify structural and cultural constraints that hinder their effective realization. Research Methodology/Design/Approach A qualitative research design employing a structured literature review was used to examine scholarly works, books, journal articles, policy documents, and official publications related to Pancasila, character development, and anti-corruption governance in Indonesia. This method enabled a comprehensive synthesis of theoretical perspectives, empirical evidence, and policy discourses concerning the integration of Pancasila values into governmental practices. Findings – The findings indicate that although awareness of the importance of Pancasila is relatively high, its implementation in the government sector remains inconsistent. Deep-rooted corruption norms, institutional inertia, limited policy enforcement, and inadequate civic oversight continue to undermine efforts to embed ethical behavior. The study also reveals that education on Pancasila values is often superficial, and community involvement in monitoring government performance remains weak. Strengthening policy interventions, improving institutional culture, and expanding public participation are essential to ensure sustainable integration of Pancasila values in public service. Originality/Value – This study provides a conceptual and contextual analysis of how Pancasila functions as an ethical foundation for anti-corruption character development in Indonesian governance. It offers actionable insights by emphasizing the need for systemic reform, value-based civil servant education, and community-driven oversight to foster a clean, transparent, and integrity-driven government.